Actualization of individual entrepreneurial potential through the transformation of educational ideas into a systemic business - Tsykhotska, Alina (Педагогічна Академія: наукові записки, 2026)
The relevance of the study is determined by the need to bridge the gap between the educational environment and business practice, which limits the effective realization of individual entrepreneurial potential and reduces the efficiency of transforming educational ideas into viable business models in a dynamic economy. The purpose of the article is to reveal the theoretical and methodological principles underlying the development of individual entrepreneurial potential and to clarify the mechanisms through which educational ideas are transformed into viable business models in a contemporary economy. Methods. The study is based on the use of methods of theoretical generalization, system analysis, structural-functional approach, and elements of comparative analysis to identify relationships between educational outcomes and entrepreneurial activity. Results. The essence of entrepreneurial potential as an integrated system of interrelated components ensuring the ability to initiate and implement business activity has been investigated. The patterns of transformation of educational ideas into business models have been identified, which are iterative in nature and based on the principles of systemacity and adaptability. Approaches to the integration of educational outcomes into entrepreneurial activity through practice-oriented mechanisms have been generalized. Key scientific and practical problems have been identified, including conceptual uncertainty, fragmentation of educational approaches, insufficient integration with the business environment, and limited support infrastructure. Conclusions. It has been proven that effective actualization of entrepreneurial potential is achieved through the combination of practice-oriented education, development of institutional support, integration with the business environment, and implementation of flexible mechanisms for business idea validation that ensure their adaptation to market conditions. Prospects for further research are associated with the development of methods for quantitative assessment of entrepreneurial potential actualization, creation of standardized models for its implementation, and analysis of the impact of the digital environment on the transformation of educational ideas into systemic business.